â€œLANTPYCATIONâ€ : METODE BARU BUDIDAYA MELON (Cucumis melo L.) RAMAH LINGKUNGAN - Daryono, Budi Setiadi (Universitas Tanjungpura, 2016)
Jamusan village is one of the areas that becomes the center of melon production at Prambanan subdistrict, Sleman, Yogyakarta. However, at this moment, the villagers of Jamusan still encountered many obstacles in melon farming. This is caused by the poor quality of the melon, crops that have not been handled well and the lack of farmerâ€™s knowledge about the management after harvesting, melon production that is not absorbed by the market. LANTPYCATION Program (Plant, Apply, and Diversification) aims to provide knowledge about quality and good management of the melons in the form of processed product diversification melon. The method applied in the implementation of this program which begins with socialization, counseling, training in management and cultivation of melons, good governance, advocacy and marketing of melon processed product. The result of the implementation of this method showed the increase of farmerâ€™s knowledge about good quality melon, farm management and procedures for the proper cultivation of melons in creating diversificated processed melon to improve the welfare of villagers Jamusan.It could be revealed that LANTPYCATION Program is a new method on sustainable agriculture of melon cultivation in Indonesia. Keywords:Melon, Melon cultivation, Diversification processed melon.